Recovery from Transient Global Amnesia Following Restoration of Hippocampal and Fronto–Cingulate Perfusion - Paolo Caffarra; Letizia Concari; Simona Gardini; Sabrina Spaggiari; Francesca Dieci; Sandra Copelli; Caterina Ghetti; Annalena Venneri (Behavioural Neurology)
A patient who suffered a transient global amnesia (TGA) attack underwent regional cerebral blood flow (rCBF) SPECT imaging and neuropsychological testing in the acute phase, after one month and after one year. Neuropsychological testing in the acute phase showed a pattern of anterograde and retrograde amnesia, whereas memory was within age normal limits at follow up. SPECT data were analysed with a within subject comparison and also compared with those of a group of healthy controls. Within subject comparison between the one month follow up and the acute phase detected increases in rCBF in the hippocampus bilaterally; further rCBF increases in the right hippocampus were detected after one year. Compared to controls, significant hypoperfusion was found in the right precentral, cingulate and medial frontal gyri in the acute phase; after one month significant hypoperfusion was detected in the right precentral and cingulate gyri and the left postcentral gyrus; after one year no significant hypoperfusion appeared. The restoration of memory was paralleled by rCBF increases in the hippocampus and fronto-limbic-parietal cortex; after one year neither significant rCBF differences nor cognitive deficits were detectable. In conclusion, these data indicate that TGA had no long lasting cognitive and neural alterations in this patient.